Improved Translational Relevance of In Vitro Fibrosis Models by Integrating IOX2-Mediated Hypoxia-Mimicking Pathways - Manuel A. González Hernández; Jennifer Venhorst; Lars Verschuren; Karin Toet; Martien P. M. Caspers; Martine C. Morrison; Beatrice Coornaert; Gerard J. P. van Westen; Roeland Hanemaaijer (Biomedicines)
Background/Objectives: Preclinical models of liver fibrosis only partially mimic human disease processes. Particularly, traditional transforming growth factor beta 1 (TGFβ1)-induced hepatic stellate cell (HSC) models lack relevant processes, including hypoxia-induced pathways. Here, the ability of a hypoxia-mimicking compound (IOX2) to more accurately reflect the human fibrotic phenotype on a functional level was investigated. Methods: Human primary HSCs were stimulated (TGFβ1 +/− IOX2), and the cell viability and fibrotic phenotype were determined. The latter was assessed as protein levels of fibrosis markers—collagen, TIMP-1, and Fibronectin. Next-generation sequencing (NGS), differential expression analyses (DESeq2), and Ingenuity Pathway Analysis (IPA) were performed for mechanistic evaluation and biological annotation. Results: Stimulation with TGFβ1 + IOX2 significantly increased fibrotic marker levels. Also, fibrosis-related pathways were activated, and hypoxia-related genes and collagen modifications, such as crosslinking, increased dose-dependently. Comparative analysis with human fibrotic DEGs showed improved disease representation in the HSC model in the presence of IOX2. Conclusions: In conclusion, the HSC model better recapitulated liver fibrosis by IOX2 administration. Therefore, hypoxia-mimicking compounds hold promise for enhancing the translational value of in vitro fibrosis models, providing valuable insights in liver fibrosis pathogenesis and potential therapeutic strategies.